2009
DOI: 10.1590/s0102-09352009000300021
|View full text |Cite
|
Sign up to set email alerts
|

Influência da interação genótipo x ambiente sobre o peso à desmama em bovinos da raça Nelore

Abstract: RESUMOAvaliaram-se os efeitos da interação genótipo x ambiente sobre a característica peso à desmama em bovinos da raça Nelore. Foram analisados 45.697 registros de peso à desmama ajustados para 205 dias, originários de três fazendas. Estas foram organizadas em duplas e analisadas por meio de análises de características únicas, considerando cada dupla como um só rebanho. Em seguida, as mesmas duplas foram submetidas a análises de características múltiplas, em que o peso à desmama de cada fazenda foi considerad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(3 reference statements)
2
3
0
4
Order By: Relevance
“…Average (± standard deviations) and maximum and minimum values for weight adjusted for weaning (W205), average daily gain from birth to weaning (ADG), and number of days for the animal to gain 160 kg from birth to weaning (D160). Comparison with other breeds yielded a similar result in the study of Ribeiro et al (2009), who analyzed data for Nelore animals, and observed an average of 198.77 kg. Guimarães et al (2003) and Fialho et al (2015) evaluated the weight at 205 days for Tabapuã and Nelore animals, respectively, and obtained lower values (170.35 and 175.59 kg) than in this study.…”
Section: Resultssupporting
confidence: 62%
“…Average (± standard deviations) and maximum and minimum values for weight adjusted for weaning (W205), average daily gain from birth to weaning (ADG), and number of days for the animal to gain 160 kg from birth to weaning (D160). Comparison with other breeds yielded a similar result in the study of Ribeiro et al (2009), who analyzed data for Nelore animals, and observed an average of 198.77 kg. Guimarães et al (2003) and Fialho et al (2015) evaluated the weight at 205 days for Tabapuã and Nelore animals, respectively, and obtained lower values (170.35 and 175.59 kg) than in this study.…”
Section: Resultssupporting
confidence: 62%
“…Faria et al (2011) não evidenciaram efeito de interação genótipo-ambiente sobre o peso à desmama em animais Nelore de seis Estados brasileiros. Ribeiro et al (2009), estudando o efeito de IGA em dados de animais Nelore de São Paulo e Mato Grosso do Sul, também não evidenciaram efeito significativo para a característica de peso à desmama. O efeito de IGA, portanto, parece mais evidente para pesos e características pós-desmama, como constatado para P450 em seis Estados do Sul, Centro-Oeste e Sudeste, por Solar Diaz et al 2011, os quais recomendaram a inclusão deste efeito na avaliação genética da característica, e por Guidolin et al (2012) em outros seis Estados, também para a raça Nelore, o que corrobora com o presente estudo nos resultados obtidos para as estimativas de herdabilidades.…”
Section: Resultsunclassified
“…Baseado no fato de que a IGA pode prejudicar o progresso genético das populações de bovinos de corte pelo uso inadequado de reprodutores, é de fundamental importância a consideração desta interação nas avaliações genéticas. (DIMOV et al, 1995), ou ainda pela comparação entre as classificações dos animais, caso sejam significativas, de acordo com os valores genéticos preditos, por meio dos vários modelos existentes (BASU & CHATTARAJI, 1988;TORAL et al, 2004;RIBEIRO et al, 2009). Mais recentemente, análise Bayesiana (FALCÃO et al, 2006;SOLAR DIAZ et al, 2011) e normas de reação via modelos de regressão aleatória (CORRÊA et al, 2009) têm sido empregadas nos estudos de IGA.…”
Section: Introductionunclassified
“…The genetic correlation of intermediate environments with favorable and unfavorable environments (+7 and -7) was basically similar (0.94). In their studies on reaction norms for growth characteristics of beef cattle, Corrêa et al (2009) and Ribeiro et al (2009) also reported variations in genetic correlation between environments and suggested a re-classification of animals according to the environmental level. Without properly accounting for these effects in genetic evaluation programs, selection for more sensitive genotypes may occur which may result in an increase of phenotypic plasticity of in their progeny.…”
Section: Resultsmentioning
confidence: 99%